Study on the Correlation Between CT Features and Vascular Tumor Thrombus Together With Nerve Invasion in Surgically Resected Lung Adenocarcinoma - Song, Yu; Chen, Daiwen; Lian, Duohuang; Xu, Shangwen; Xiao, Hui (Frontiers in Surgery, 2022)
Background: We aimed to analyze the relationship between pulmonary adenocarcinoma patients with vascular tumor thrombus and nerve invasion and different CT features. Methods: The preoperative CT scanning data of 86 patients with lung adenocarcinoma who underwent surgical resection in our hospital from January 2020 to January 2022 were analyzed in the form of retrospective analysis. The CT images of all patients were observed and the relationship between them and vascular tumor thrombus and nerve invasion of lung adenocarcinoma was analyzed. At the same time, the sensitivity, specificity and accuracy of enhanced CT and plain CT were compared to evaluate the diagnostic efficacy of both. Results: The results showed that the vascular tumor thrombus of lung adenocarcinoma was mainly related to the solid components, lobulated and calcified tumors in CT images, and the nerve invasion of lung adenocarcinoma was mainly related to the tumors with bronchial inflation sign in CT images (P < 0.05). The sensitivity, specificity and accuracy of enhanced CT in the diagnosis of vascular tumor thrombus were 78.26%, 96.83% and 91.86% respectively, and the sensitivity, specificity and accuracy in the diagnosis of nerve invasion were 75.00%, 98.72% and 96.51% respectively. The sensitivity, specificity and accuracy of plain CT in the diagnosis of vascular tumor thrombus were 43.48%, 92.06% and 79.07% respectively, and the sensitivity, specificity and accuracy in the diagnosis of nerve invasion were 25.00%, 94.87% and 88.37% respectively. The contrast showed that the sensitivity and accuracy of enhanced CT were higher than that of plain CT (P < 0.05), but the difference of specificity was not obvious (P > 0.05). Conclusions: Solid components, lobulated and calcified tumors in CT signs are closely related to vascular tumor thrombus of lung adenocarcinoma, while patients with bronchial inflation sign are related to nerve invasion.